2002
DOI: 10.1021/ja029116g
|View full text |Cite
|
Sign up to set email alerts
|

Resorcinarenes as Templates:  A General Strategy for the Synthesis of Large Macrocycles

Abstract: The concept that resorcinarenes can be used as templates for the synthesis of large macrocycles is introduced. By way of example, previously inaccessible, aromatic crown ethers compounds are synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…2 Preorganisation can be achieved also via covalent attachment to a suitable template molecule, 3 as shown recently by the spectacular synthesis of cyclic phenol ethers. 4 The situation is even more complicated, if several covalent links have to be formed within a precursor molecule in a well defined way. High dilution alone, preventing intermolecular reactions, cannot be used to suppress undesired intramolecular connections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Preorganisation can be achieved also via covalent attachment to a suitable template molecule, 3 as shown recently by the spectacular synthesis of cyclic phenol ethers. 4 The situation is even more complicated, if several covalent links have to be formed within a precursor molecule in a well defined way. High dilution alone, preventing intermolecular reactions, cannot be used to suppress undesired intramolecular connections.…”
mentioning
confidence: 99%
“…High dilution alone, preventing intermolecular reactions, cannot be used to suppress undesired intramolecular connections. Take as an example a calix [4]arene fixed in the cone conformation in the form of its tetraether and functionalized at the wide rim. Intramolecular connection of these functional groups by a bifunctional reagent will lead in 2 3 of all cases to a bridging of adjacent phenolic units and in 1 3 to a transcavity bridging between opposite units § (Fig.…”
mentioning
confidence: 99%
“…This corresponds to a 50 % yield starting from the readily available resorcinarene 1 (R CH 2 CH 2 Ph) and commercially available 3,5-dibromobenzaldehyde. The [32]crown-8 5 has not been previously reported, and so a precise measure of the efficiency of this templation protocol cannot be determined. As a gauge however, we can note that the smaller, unfunctionalized analogues 6 and 7 were prepared by means of step-wise protocols that gave overall yields in the sub 0.1 % range.…”
Section: Resorcinarenes As Templatesmentioning
confidence: 97%
“…[32] These unique macrocycles undoubtedly fit the first criteria of availability, although more research is necessary to determine if they can also fulfill the criteria of adaptability. If they can, they may be able to extend the envelope of readily available macrocycles ™beyond∫ [18]crown-6.…”
Section: Resorcinarenes As Templatesmentioning
confidence: 98%
“…As well as proving to be useful hosts, these deep-cavity cavitands also demonstrated that resorcinarenes could be used as covalent templates to form macrocycles. For example, the deep-cavity cavitand shown in Scheme 8 can be treated with excess BBr 3 to cleave the four, benzal-bridges and liberate a new family of aromatic macrocycle [ 25 ]. Interestingly, as these hosts are tetra-acetals we initially tried removing the template under acidic conditions.…”
Section: Reviewmentioning
confidence: 99%